Pengaruh Penggunaan Metode Pembelajaran Moral dan Tingkat Religiusitas Terhadap Peningkatan Pertimbangan Moral - Samsul Susilawati (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
The use of appropriate moral learning methods will be better able to improve students' moral considerations. This research is an experimental research with a 2 x 2 factorial experimental design. The subjects of this study were students of the Faculty of Tarbiyah and Teacher Training, UIN Maliki Malang, majoring in the second semester of PGMI. The number of students as research subjects was 159 students, consisting of classes; IIA, IIB, IIC, IID. The determination of the class to be the research subject was carried out randomly. The random procedure was carried out in two stages, namely random selection and random assignment. The study was conducted in a span of 8 meetings, namely March 18 to May 6, 2013. The results showed that (1) the level of moral consideration of students taught using the moral dilemma discussion method was significantly different, when compared to students taught using the question-lecture method. answer. (2) The level of moral consideration in the subject of high religiosity is significantly different, when compared with the subject of low religiosity. (3) There is no interaction between method use and religiosity towards the level of student moral considerations.